TATA KELOLA PEMERINTAH DALAM PENATAAN PEDAGANG KAKI LIMA STUDI KASUS CAR FREE DAY BOULEVARD KOTA MAKASSAR - Rahman, Abd; Mappiwali, Hermawati; Sufriaman, Sufriaman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study analyzes the governance of Makassar City government in managing street vendors (PKL) in the Car Free Day (CFD) Boulevard area. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews with 10 informants, and documentation studies. Data analysis refers to the Miles and Huberman interactive model, focusing on three policy implementation dimensions. The findings reveal that: (1) The level of problem controllability is moderate, characterized by the implementation of northern zoning for street vendors and southern zoning for sports activities, along with restricted trading hours from 06.00 to 11.00 WITA; (2) Policy formulation precision remains suboptimal due to the absence of Mayoral Regulations or SOPs, resulting in inconsistent policy implementation; (3) External factors including street vendors' economic pressures, visitor dynamics, and limited monitoring capacity significantly affect arrangement effectiveness. The study concludes that strengthening formal regulations, enhancing inter-agency coordination, and adopting adaptive approaches to street vendors' socio-economic conditions are essential for optimizing street vendor governance in CFD public spaces